Perancangan Kampanye Digital Pencegahan Anemia untuk Perempuan Usia 16-19 Tahun di Surabaya - Andini, Defina Novita; Chidtian, Aileena Solicitor Costa Rica El; Daniar, Aninditya (Metta : Jurnal Ilmu Multidisiplin, 2024)
Anemia occurs due to a condition of lack of red blood cells or hemoglobin. Factors that can affect a person affected by Anemia such as an unhealthy and unbalanced diet to the lack of knowledge of women about Anemia.  Prevention can be done by holding an Anemia prevention campaign for women aged 16-19 years who live in Surabaya. The campaign is carried out in a fun and cheerful way that suits the interests of young women aged 16-19 years old today, especially through social media. The media designed uses main media and various supporting media.  The design was carried out using qualitative and quantitative research methods. Data acquisition is done through primary and secondary data. Primary data is done by interview and observation. Secondary data is obtained from literature studies and literature studies. The results of the data that have been collected are then analyzed using fishbone analysis. The results of the fishbone analysis are continued to obtain keywords or big ideas that are used as the initial design concept. Keywords are developed to become visual concepts, character concepts, and media concepts. The design concept features design colors that combine the color concepts of health and cheerfulness. The character concepts used are women aged 16-19 years and nutritionists. Visuals are presented with a combination of vectors and illustrations as well as sans serif typography and layouts. The campaign aims to change the behavior and lifestyle patterns of adolescent girls to be healthy and balanced and increase awareness of the importance of preventing Anemia. The overall design of the campaign is an effective strategy in increasing awareness and knowledge about Anemia through the delivery of interesting information and appropriate learning so as to change behavior related to health.